PENGARUH KOMITE AUDIT, DEWAN KOMISARIS INDEPENDEN DAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK DI PERUSAHAAN KEUANGAN - St. Nur Fadilah; Lia Rachmawati; Muhaimin Dimyati (Jurnal Ilmiah Akuntansi Indonesia, 2021)
This study aims to examine and analyze the effect of the audit committee, independent board of commissioners, and capital intensity on tax avoidance as measured by the Cash Effective Tax Rate (CETR). The population used in this study are financial companies listed on the Indonesia Stock Exchange during 2015 to 2019. The analysis techniques used in this research are classical assumption test, multiple linear regression analysis, determination coefficient test and hypothesis test. The results showed that partially the audit committee and independent board of commissioners had an effect on tax avoidance, while capital intensity had no effect on tax avoidance. Simultaneously, it shows that the audit committee, independent board of commissioners, and capital intensity have an effect on tax avoidance.